Feasible synthesis of coal fly ash based porous composites with multiscale pore structure and its application in Congo red adsorption. (July 2022) - Sun, Guangchao; Zhang, Jiayu; Hao, Bianlei; Li, Xiang; Yan, Mingwei; Liu, Kaiqi
Abstract: Facing the great challenge that the increasing solid waste fly ash is difficult to treat and utilize properly, this paper reports a class of novel low–cost fly ash porous materials with high interconnected porosity fabricated by a facile foaming process. On this basis, composites with multiscale pore structures from the nanometer to macroscopic scale were designed and constructed by decorating layered double hydroxide (LDH) onto the inner channel surface. Such porous materials with 3D through–hole structures showed high interconnected porosity (up to 77.61%), suitable compressive strength (up to 23.79 MPa) and significant water permeation flux (549.86 m 3 ∙m −2 ∙h −1 at 0.1 MPa). Moreover, the adsorption effect of dosage, initial concentration, pH, temperature and contact time on Congo red (CR) from simulated wastewater was investigated. The composites exhibited a good adsorption efficiency of ∼100% and adsorption capacities of 45.79 mg/g. The adsorption kinetic can be explained well by the pseudosecond–order kinetic equation and isotherm adsorption followed Langmuir isotherm model. This suggests that low–cost and eco–friendly fly ash composites have potential applications in industrial–scale wastewater treatment. This work also provides a general strategy to design and utilize fly ash porous materials for filtration and adsorption. Graphical abstract: Image 1 Highlights: Fly ash based composite with multiscale pore structure was fabricated. The composite exhibits high interconnected porosity and water permeation flux. Layered double hydroxide decorated composite has good adsorption effect for Congo red. The adsorption curves follow the pseudo-second kinetic model and Langmuir model. Low-cost and eco-friendly fly ash composite shows excellent cost performance.